Kontrak Kerjasama Penggarapan Lahan Kayu Putih Perspektif Fiqh Muzara’ah (Studi Kasus Perum Perhutani KPH Madiun Dan Petani LMPSDH Sido Luhur Desa Kaponan Kecamatan Mlarak Kabupaten Ponorogo) - Afifah, Hiyarotul; Hasan Wahid, Soleh (Institut Agama Islam Negeri Ponorogo, 2021)
In the village of Kaponan, Mlarak, Ponorogo, Not all people who farm have their own agricultural land There are several farmers who do not have their own land, collaborating with parties who have a lot of land to carry out agricultural activities. Some of the community members manage the land belonging to the KPH Madiun (Kesatuan Pengelolaan Hutan). At first the collaboration took place verbally, but along with the times, agreements were made in writing to facilitate arrangements. So that the amendment to this agreement raises several opinions, there are parties who think that verbally agreements are more suitable to be applied and there are also parties who think that written agreements are more suitable. Based on the description above, the researcher used two problem formulations in this study. (1) How is the application of Islamic agreement principles in the eucalyptus land cultivation cooperation contract between Perum Perhutani KPH Madiun and LMPSDH Sido Luhur Kaponan, Mlarak, Ponorogo according to Fiqh Muzara’ah. (2) How is the clause of the cooperation contract for the cultivation of eucalyptus land between Perum Perhutani KPH Madiun and LMPSDH Sido Luhur Kaponan, Mlarak, Ponorogo Regency according to Fiqh Muzara’ah. According to the type, this research includes field research using qualitative methods. While the data collection techniques used are observation, interviews and documentation. The analysis used is the inductive method, which is a method that emphasizes previous observations, then draws conclusions based on these observations. From the results of this study it can be concluded that what is more appropriate in the application of the principles of Islamic agreement is when this agreement is made verbally. Because all parties have implemented all the principles of Islamic agreement, there are only two principles of Islamic agreement that have not been implemented. While the level of validity in the application of fiqh Muzara’ah refers to an agreement that occurs in writing, because the pillars and requirements of Muzara’ah have been fulfilled in their entirety.